Weeknights with Giada : quick and simple recipes ot revamp dinner - De Laurentiis, Giada (Clarkson Potter, 2012)
Food Network star Giada De Laurentiis delivers soups, sandwiches, pizzas, pastas, and meat and fish dishes that come together quickly as stand-alone main courses--most in half an hour or less.